2013
DOI: 10.1017/s1368980013002504
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating free school fruit: results from a natural experiment in Norway with representative data

Abstract: Objective: To assess impacts of the nationwide Norwegian School Fruit Scheme (NSFS) using nationally representative data. Design: The NSFS is organized such that primary-school children (grades 1-7) are randomly assigned to one of three school fruit arrangements: (i) the child receives one free fruit or vegetable per day; (ii) the child is given the option to subscribe to one fruit or vegetable per day at a subsidized price; and (iii) the child attends a school that has no school fruit arrangement. Setting: Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…However, that study did not use a control group, limiting the ability to attribute the increased fruit consumption to the program. Also, in line with our present results, previous evaluation studies of the NSFS have also confirmed that the program increased fruit but not vegetable consumption among children, regardless of gender and SES [22,23].…”
Section: The Nsfs Effect On Dietary Behavioursupporting
confidence: 92%
See 1 more Smart Citation
“…However, that study did not use a control group, limiting the ability to attribute the increased fruit consumption to the program. Also, in line with our present results, previous evaluation studies of the NSFS have also confirmed that the program increased fruit but not vegetable consumption among children, regardless of gender and SES [22,23].…”
Section: The Nsfs Effect On Dietary Behavioursupporting
confidence: 92%
“…Among children, school-based intervention studies aiming to increase fruit and/or vegetable consumption have shown promising effects during their operation [20,21]. In Norway, two separate evaluation studies of the NSFS have shown that the program increased fruit consumption among children, regardless of gender and SES [22,23]. Additionally, a pilot version of the NSFS seemed to reduce the consumption of snacks among children while operating [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, providing free fruits to the youngest Norwegian pupils increased these pupils' intake of fruits with 25% compared to pupils who did not receive this offer. More surprisingly, the parents' intake increased with 12.5% as well (Øvrum and Bere, 2014). Adoption of health interventions/changes as 'main stream' by a small population (e.g., children accept "Thursday Veggieday" without problems (De Keyzer et al, 2012)), may eventually result in adoption by the general public as well.…”
Section: Micro-environmental Influencesmentioning
confidence: 99%
“…Issues of sustainability outside of the school settingincluding maintenance of a supply of fruit and vegetables at a reasonable cost to government and establishment of systems for ordering, collecting and distributing fruit and vegetables to schoolswould obviously need to be addressed if this pilot intervention were scaled up. Government-funded programs of this kind are successfully implemented in many countries, [4][5][6][7][8] however, indicating that sustainability should not be an issue. Furthermore, a larger variety of fruit and vegetables would need to be accessed in order to achieve all of the objectives of the C&S programa need that was raised by some school contacts in this study.…”
Section: Box 1 Example Quotes From the Post-intervention Key School mentioning
confidence: 99%
“…Government-funded programs that provide free fruit or free fruit and vegetables in schools have been implemented in many countries including England, 4 Canada, 5 Norway, 6 the Netherlands 7 and New Zealand, 8 resulting in increased overall fruit consumption, children's acceptance of and willingness to try new varieties of fruit and vegetables, and increased preferences for fruit. This pilot study aimed to examine the feasibility, acceptability and efficacy of the provision of supplementary, free fruit and vegetables in supporting equitable participation in the C&S program.…”
Section: Introductionmentioning
confidence: 99%